The Effect of Ratio of Red Kidney Bean and Oyster Mushroom with Addition Tapioca and Taro Flour on the Quality of Sausage - Elva Amurita Zebua; Herla Rusmarilin; Lasma Nora Limbong (Universitas Sumatera Utara, 2014)
The aim of this research was to find the effect of red kidney bean and oyster mushroom with addition tapioca and taro flour on the quality of sausage. The research was using completely randomized design with two factors, i.e ratio of red kidney bean and oyster mushroom (A): (100%:0%, 75%:25%, 50%:50%, and 25%:75%) and ratio of tapioca and taro flour (T): (100%:0%, 75%:25%, 50%:50%, 25%:75%, and 0%:100%). Parameter analyzed were moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of colour, flavor, taste, and texture. The results showed that the ratio of red kidney bean and oyster mushroom had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of colour, flavor, taste, and texture. The ratio of tapioca and taro flour had highly significant effect on ash content, fat content, protein content, crude fiber conten, organoleptic value of colour, dan texture. Interaction of the two factors had highly significant effect on protein content and organoleptic value of taste, and had significant effect on organoleptic value of colour. The ratio of red kidney bean and oyster mushroom of 75%:25% with addition tapioca and taro flour of 25%:75% produced the best sausage. Keywords: oyster mushroom, red kidney bean, sausage, tapioca, taro flour